Chorioamnionitis exposure remodels the unique histone modification landscape of neonatal monocytes and alters the expression of immune pathway genes. (22nd December 2018) - Bermick, Jennifer; Gallagher, Katherine; denDekker, Aaron; Kunkel, Steve; Lukacs, Nicholas; Schaller, Matthew
Abstract : Chorioamnionitis is an intrauterine infection involving inflammation of the chorion, amnion, and placenta. It leads to a fetal systemic inflammatory response that can alter the transcription of neonatal immune genes. We have previously shown that neonatal monocytes gain the activating histone tail modification H3K4me3 at promoter sites of immunologically important genes as development progresses from preterm neonate to adult. In this study, we applied ChIP‐seq and RNA‐seq to evaluate the impact of chorioamnionitis on the neonatal monocyte H3K4me3 histone modification landscape over the course of fetal and neonatal immune system development. Chorioamnionitis exposure in neonatal monocytes resulted in a net increase in total monocyte H3K4me3, primarily in introns and intergenic regions. Immune gene expression was decreased in chorioamnionitis‐exposed monocytes, with the majority of enriched transcripts falling into pathways that are not linked to the immune system. Over half of all neonatal monocyte H3K4me3 peaks, independent of their location, were associated with active gene transcription. Overall, chorioamnionitis exposure resulted in the global remodeling of the neonatal monocyte H3K4me3 landscape and changes in the expression of known immune genes. These changes resulted in a less robust inflammatory response upon exposure to a secondary challenge, which may explain why chorioamnionitis‐exposed neonates have an increased risk of sepsis. Database: ChIP‐seq data for U30/O30/Term: GEOGSE81957 ChIP‐seq data for U30C/O30C/TermC: GEOGSE111873 RNA‐seq data for U/L/CU/CL: GEOGSE111927 Abstract : Exposure to chorioamnionitis, a common intrauterine infection, alters the neonatal monocyte histone modification landscape. Specifically, the activating histone modification mark H3K4me3 is removed from promoters and instead enriched in introns and intergenic regions. This results in reduced expression of immune pathway genes, leading to a decreased inflammatory response when a secondary immune stimulus is encountered.